2010
DOI: 10.14227/dt170310p34
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Floating Gelucire Matrices of Metoprolol Succinate

Abstract: The aim of the current investigation was to formulate floating sustained-release matrices of metoprolol succinate using Gelucire 43/01 and Gelucire 44/14 by a melt-solidification technique. The in vitro and in vivo characteristics of the prepared matrices were evaluated. The in vitro drug release studies performed in 0.1 N HCl revealed a proportional increase in drug release pattern with increased concentration of Gelucire 44/14.Drug release data were analyzed by various mathematical models, and the mean disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is used to treat hypertension and various cardiovascular disorders. It is chemically known as (±) 1-(isopropyl amino)-3-[p-(2-methoxyethyl) phenoxy]-2-propanol succinate (2:1) (Gad, 2014;Siripuram et al, 2010). Cilnidipine Figure 1b is chemically 1,4-dihydro-2,6-dimethyl-4-(3-nitrophenyl)-3,5pyridine carboxylic acid-2methoxy ethyl-(2E)-3-phenyl-propenylester (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat hypertension and various cardiovascular disorders. It is chemically known as (±) 1-(isopropyl amino)-3-[p-(2-methoxyethyl) phenoxy]-2-propanol succinate (2:1) (Gad, 2014;Siripuram et al, 2010). Cilnidipine Figure 1b is chemically 1,4-dihydro-2,6-dimethyl-4-(3-nitrophenyl)-3,5pyridine carboxylic acid-2methoxy ethyl-(2E)-3-phenyl-propenylester (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Glycerideconjugated lipids are available with varying degrees of hydrophobicity and melt at low temperatures to aid in thermal processing, making them ideal carriers for controlled drug delivery (Aiṅaoui and Vergnaud, 1998). Siripuram et al demonstrated the sustained release properties of Gelucire® 43/01 (Siripuram et al, 2010).…”
Section: Introductionmentioning
confidence: 99%